alarm
Ask a question for free
Math
Rebecca Foster

Subtract a2+ 2a -3 from 3a2– 2a +4​

answers: 1
Register to add an answer
Answer:

hello dear here is your answer hope it helps you have a great day

1a² + 2a – 24 = 0

multiply the 1st & 3rd variable= (-24). two numbers that equal -24 when multiplied& 2(middle variable) when added/subtracted= (6 & - 4)

rewrite using the new “middle” terms...

1a² + 6a – 4a – 24 = 0

(1a² + 6a) – (4a – 24) = 0

a(a + 6) – 4(a+6) = 0

RULE- the terms in parenthesis have to match- combine it(once) with outer terms

(a – 4)(a + 6) = 0

a – 4 = 0

add 4 to both sides (opposite of subtraction/negative #)

a – 4 + 4 = 0+4

a = 4

a + 6 = 0

a+6 - 6 = 0- 6

a = -6

solutions: 4, -6

67
Larssen
For answers need to register.
Contacts
mail@expertinstudy.com
Feedback
Expert in study
About us
For new users
For new experts
Terms and Conditions